(untitled) (Fiep Bulletin - online, 2013)
The spinal cord injury (SCI) is one of the most serious syndromes that can achieve the human being, it causes failure of a number of vital functions. Knowing that the hospitalization causes changes in the general patient and family, we identify important bibliographies that portray the (SCI) as a cause of the long hospital stay. OBJECTIVE: To identify the TRM in the literature as a factor in long-term hospitalization and the actions undertaken by the nursing staff. METHODOLOGY: Search the literature of the last ten years from the databases of BIREME and LILACS, with the descriptors of spinal cord trauma hospital X, which found 02 articles, and spinal cord trauma nursing X with 21 articles. The same descriptors were used in BDENF, identifying 14 articles. For the selection of the articles were considered the following inclusion criteria: neurological patients and have been hospitalized for more than three months. RESULTS: In Brazil, 40 new cases annually per million inhabitants with a total of 8 thousand cases a year where more than 50% of these require hospitalization, which is the approximate cost of 300, 000, 000.00 per year. The long stay in bed interferes with the rehabilitation, increasing the length of hospitalization with overall mortality estimated at 24% which reflect the degree of care and knowledge of nursing. Stress the importance of physical care and prevention of complications to prevent long hospital stay that has as its main causes the sensitive and sphincter disorders and related injuries in other organs or systems. CONCLUSION: We believe that the articles dealing with the damage caused by long hospital stay (LPH) are restricted. Generally addressing other factors as being responsible for long-stay patient in the hospital. The texts obtained only two attribute as a factor of LPH complications arising from systemic infections such as SCI.